Safety, Effectiveness, Grading Of Operative Difficulty And Timing Of Laparoscopic Cholecystectomy For Gallbladder Empyema: Single Institutional Study - Aravindhan, Aravindhan; Shyamsundar, S.R.; Hameed, Fareed Ul; M. Ramula, M. Ramula (Journal of Neonatal Surgery, 2025)
Background: Empyema of the gallbladder is one of the frequently encountered severe forms of acute cholecystitis. It usually starts with acute cholecystitis progressing to a fulminant nature, with biliary stasis and obstruction of cystic duct. This results in a surgical emergency and needs immediate optimisation and urgent removal of the gallbladder to reduce the risk of sepsis with resulting morbidity and mortality. Patients with gallbladder empyema require urgent cholecystectomy or cholecystostomy tube drainage of pus, based on the severity of symptoms and clinical presentation at the time of admission. Aim: To determine and grade the degree of intra-operative difficulty in managing. To choose the various modalities of management, such as laparoscopic cholecystectomy, laparoscopic subtotal cholecystectomy, laparoscopic tube cholecystostomy and open cholecystectomy. Patients and Methods: A prospective observational study of 50 patients to observe the safety, effectiveness, and feasibility of laparoscopic cholecystectomy for empyema gall bladder for 2 years. Preoperative investigations, intra-operative findings, duration of surgery, grading of difficulty during surgery, post-operative recovery, and number of days in the hospital are analysed. Results: By grading the severity of the pathology by intra-operative findings the surgeon can anticipate the difficulty of performing the procedure and decide which is the safe modality to choose for the patient. Post-operative complication rates are irrespective of approach either laparoscopic or open, is higher for empyema gall bladder. Surgeons who undertake laparoscopic approaches should have a low threshold to convert to open procedures when they encounter technical difficulties. Conclusion: Surgeons who undertake laparoscopic approaches should have a low threshold to convert to open procedures when they encounter technical difficulties. Thus, this study shows that the laparoscopic approach is safe and effective in the management of empyema gallbladder.